PEMBUKTIAN TERHADAP TINDAK PIDANA KEJAHATAN PENJUALAN OBAT KESEHATAN IMPOR - Aaron William Pantow; Chionya Sherly Mahat; George Vitto Corleone Sitorus; Grace Margareth Simarmata; Jessica Gabriela Chandra Gunawan; Keren Angeline Manoppo (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research examines the evidentiary process in cases of illegal imported health drug sales in Indonesia, focusing on challenges emerging in the digital era. Using a qualitative approach with a case study design, this study analyzes the complexities of evidence gathering, the existing legal framework, and factors facilitating such crimes. The findings indicate that the effectiveness of evidence collection heavily depends on a multidisciplinary approach and digital forensic capabilities. Key challenges include gaps in law enforcement capacity, legal frameworks that have not accommodated technological advancements, and the complexity of cross-border cases. The study recommends forming multidisciplinary teams, enhancing digital forensic capacities, revising legislation, strengthening international cooperation, and implementing innovative technologies such as blockchain. In conclusion, effective handling of illegal imported drug sales requires a holistic approach integrating legal, technological, and public health aspects.